IMPLEMETASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK PEMBENTUKAN KARAKTER GOTONG ROYONG PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD NEGERI JANTEN KULON PROGO - GALIH ADI PANGESTU; Nadziroh Nadziroh; WACHID PRATOMO (Jurnal Sosio dan Humaniora (SOMA), 2026)
This study aims to provide an in-depth description of how the Problem Based Learning (PBL) model is implemented to foster the value of mutual cooperation in the Pancasila Education subject for fourth-grade students at SD Negeri Janten, Kulon Progo. The research was conducted in the fourth-grade classroom of SD Negeri Janten from July 2025 to February 2026. The participants included the school principal, the fourth-grade teacher, and fourth-grade students who were directly involved in the learning process. Data were collected through observations, interviews, and documentation. To support the data collection process, the researcher employed observation guidelines, interview guidelines, and documentation as research instruments. The validity of the data was ensured through credibility testing using triangulation techniques to enhance the accuracy and trustworthiness of the findings. Furthermore, the data were analyzed using the Miles and Huberman analysis model, which consists of data collection, data reduction, data display, and conclusion drawing or verification. The results of the study indicate that the implementation of the Problem Based Learning model in Pancasila Education was carried out by presenting real-life problems found in the school environment as discussion material and group work activities. The teacher played an active role in providing guidance, supervision, and assistance throughout the learning process to help students develop caring attitudes, empathy, and cooperation as manifestations of the mutual cooperation character. The inhibiting factors in implementing this learning model included students’ individualistic attitudes, excessive independence, and environmental influences. Meanwhile, the supporting factors included adequate teaching staff, the appropriate application of the learning model, and good cooperation between teachers and parents. To overcome these obstacles, teachers utilized intra-curricular and extracurricular school activities and consistently applied the Problem Based Learning (PBL) model in the classroom to strengthen the development of students’ mutual cooperation character.